A Historical Review of Efforts in the Area of Management Semantics - Bedeian, Arthur G. (Academy of Management Journal, 1974)
An evaluation of efforts designed to aid in the alleviation of the terminological conflicts existing within the field of management is presented in this paper. Included are reviews of both currently available and out-of-print general management dictionaries and glossaries.